2004
DOI: 10.1111/j.1365-2125.2004.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide in active rheumatoid arthritis: a prospective study in daily practice

Abstract: AimsWe prospectively studied the efficacy, incidence of adverse drug reactions and withdrawal from leflunomide in an outpatient population with rheumatoid arthritis in a setting of care-as-usual. MethodsIn this prospective case series study, from outpatient medical records a standard dataset was collected including patient and disease characteristics, data on leflunomide use and adverse drug reactions. ResultsDuring the study period 136 rheumatoid arthritis patients started leflunomide. Median (range) follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
2
16
1
1
Order By: Relevance
“…With combination for three be effective and safe in general practice. [27] resistant RA, provided regular monitoring of months, there was improvement in 9(91%) Weekly use and even omitting the loading liver function and hematological parameters and remission in 1 (9%), respectively. Efficacy dose, has shown comparable efficacy to daily are performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With combination for three be effective and safe in general practice. [27] resistant RA, provided regular monitoring of months, there was improvement in 9(91%) Weekly use and even omitting the loading liver function and hematological parameters and remission in 1 (9%), respectively. Efficacy dose, has shown comparable efficacy to daily are performed.…”
Section: Discussionmentioning
confidence: 99%
“…Zero, 7 (8%), 77 (92%) and 0,6 (10%), 54 (90%) patients with mild, moderate and high disease severity respectively, were included in the ITT and PP analysis. Twenty (24%), 45 (54%), 51 (61%) and 12 (20%), 37 (62%), 38 (63%) patients at baseline, 3 and 6 months showed rheumatoid factor negativity by ITT analysis (Chi value=25.91, df=2, P<0.001) and PP 9 (11) 8 (13) 9 (15) 1 (9) 3 (27) (1-6)*** analysis (Chi value=28.97, df=2, P <0.001), respectively. Secondary efficacy parameters also improved from three months [ Table 3].…”
Section: Methodsmentioning
confidence: 99%
“…Failure rates have been reported between 55.5% and 56.2% per 100 patient years' follow-up [6,7]. Furthermore, Geborek et al [8] and Siva [9] reported withdrawal from leflunomide treatment of 78% of patients after 20 months' and 63% after 6 months' follow-up, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Results of an observational study in patients with RA on leflunomide treatment showed that the characteristics of patients treated in a setting of care-as-usual differ from characteristics of the populations in RCTs, suggesting channelling of the application of leflunomide [6]. Compared with the population included in the RCTs on leflunomide, the population in this study had a higher age, had longer disease duration, and was more intensively treated with disease-modifying antirheumatic drugs (DMARDs) before starting leflunomide.…”
Section: Introductionmentioning
confidence: 99%
“…Это лефлуномид (ЛФ, Арава) и биологические препараты (БП). Поскольку опыт практического исполь-зования новых препаратов был невелик, а стоимость их -довольно высока, они назначались в тех случаях, когда другие противоревматические средства оказались неэф-фективными [2]. Наличие большого количества таких больных и высокая эффективность новых лекарственных средств обеспечили им широкую популярность.…”
unclassified